UJI AKTIVITAS ANTIFUNGAL EKSTRAK KULIT PISANG BARANGAN (MUSA ACUMINATA COLLA.) TERHADAP PERTUMBUHAN JAMUR PITYROSPORUM OVALE - Chandra, Fioni; Lister, I Nyoman Ehrich (BIOLINK : Jurnal Biologi Lingkungan, Industri dan Kesehatan, 2019)
Clean and Healthy Lifestyle is essential to be endeavored by society for preventing variety of infectious diseases which one of the most common is dandruff or seborrhea sicca that caused by the growth of Pityrosporum ovale fungi. This research is indicated to provide a better alternative option using ingredient given by nature that can treat dandruff. This research using banana peel extract since it is an original fruit from North Sumatra. The result from phytochemical screening of the banana peel extract shows secondary metabolites which are saponin, tannin, steroid/tritepenoida, flavonoid and glycosides. To produce barangan banana peel extract is by maseration method. Antifungal activity test using barangan banana peel extract towards Pityrosporum ovale is done by disc diffusion method. The antifungal activity test shows the biggest result for Minimum Inhibitory Concentration (MIC) extraction concentration at 1000 mg/ml with the average diameter of 11,9 mm. According to the inhibitory scale of antifungal activity test of barangan banana peel extract towards the growth of Pityrosporum ovale is ineffective.